Analisis penggunaan website jatim travel monitor sebagai sarana pendukung pendapatan asli daerah di Jawa Timur - Nanda Novitasari; Renny Oktafia (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
East Java has very diverse tourism where this sector can support Regional Original Income (PAD) through tourist fees. The obstacles faced in the tourism sector in East Java are the absence of data collection, tourism registration still uses a manual process, and is not updated in real time and there is no platform that can reach thousands of Tourist Attractions. There is a need for development in the tourism sector, one of which is through digitalization efforts, as was done by the East Java Culture and Tourism Office by presenting a website called Jatim Travel Monitor as a means of supporting Regional Original Income in East Java. The purpose of this study is to analyze the extent to which the website can be used as a means of supporting local revenue (PAD) through tourism fees. This study uses a qualitative method with a case study approach. Collecting data using interviews, observation, and documentation. The results obtained from this research are that the Jatim Travel Monitor Website can facilitate tourism managers and agencies in formulating and increasing local revenue (PAD) through tourist fees and monitoring the number of visits generated which can be used as a reference as a support for increasing tourist visits so that genuine income Regional (PAD) increased